Kilohertz Pulsed‐Laser‐Polymerization: Simultaneous Determination of Backbiting, Secondary, and Tertiary Radical Propagation Rate Coefficients for tert‐Butyl Acrylate. Issue 9 (14th March 2016) - Wenn, Benjamin; Junkers, Thomas
Abstract : For the first time, a 1000 Hz pulse laser has been applied to determine detailed kinetic rate coefficients from pulsed laser polymerization–size exclusion chromatography experiments. For the monomer tert ‐butyl acrylate, apparent propagation rate coefficients k p app have been determined in the temperature range of 0–80 °C. k p app in the range of few hundreds to close to 50 000 L·mol –1 ·s –1 are determined for low and high pulse frequencies, respectively. The apparent propagation coefficients show a distinct pulse‐frequency dependency, which follows an S‐shape curve. From these curves, rate coefficients for secondary radial propagation ( k p SPR ), backbiting ( k bb ), midchain radical propagation ( k p tert ), and the (residual) effective propagation rate ( k p eff ) can be deduced via a herein proposed simple Predici fitting procedure. For k p SPR, the activation energy is determined to be (17.9 ± 0.6) kJ·mol –1 in excellent agreement with literature data. For k bb, an activation energy of (25.9 ± 2.2) kJ·mol –1 is deduced. Abstract : A simple, but robust evaluation method for pulse‐frequency‐dependent pulsed laser polymerization–size exclusion chromatography data for acrylate monomers is presented and secondary radical propagation, backbiting, and midchain radical propagation rate coefficients for tert ‐butyl acrylate in the temperature interval of 0–80 °C are provided.